Trophic Requirements of the Sea Urchin Paracentrotus lividus Varies at Different Life Stages: Comprehension of Species Ecology and Implications for Effective Feeding Formulations - Grosso, Luca; Rakaj, Arnold; Fianchini, Alessandra; Tancioni, Lorenzo; Vizzini, Salvatrice; Boudouresque, Charles-François; Scardi, Michele (Frontiers in Marine Science, 2022)
The progressive increase in size after the metamorphosis leads to a consequent variation of trophic requirements and food energy allocation in the sea urchin Paracentrotus lividus. In fact, protein and/or carbohydrate requirements vary widely during the different life stages, in response to changes in the energy allocation from somatic growth to reproductive investment. Investigations on the food quality and quantity requirements in each life cycle stage are therefore crucial for the artificial rearing of sea urchins. The future success of echinoculture depends heavily on the development of suitable and cost-effective diets that are specifically designed to maximize somatic growth during the early life stages and gonadal production in the later stages. In this context, a considerable number of studies have recommended animal sources as supplements in sea urchin diets. However, with the exception of Fernandez and Boudouresque (2000), no studies have compared the dietary requirements over the different life stages of the sea urchin. In the present study, the growth and nutrition of three life stages of P. lividus (juveniles: 15-25 mm; subadults: 25-35 mm; adults: 45-55 mm) were investigated over a 4-month rearing experiment. Three experimental diets, with 0%, 20% and 40% of animal-sourced enrichments, were tested in parallel for the three life stages. The food conversion ratio, somatic and gonadal growth were assessed in each condition in order to evaluate the optimal level of animal-sourced supplements for each life stage. A general growth model covering the full post-metamorphic P. lividus life cycle was defined for each experimental diet. Our results evidenced that P. lividus, during the juvenile stage, requires higher animal supply (40%), while a feeding requirement shift takes place toward lower animal supply (20%) in sub-adult and adult stages. This study sheds light on P. lividus trophic ecology, broadening our basic knowledge of the dietary requirements of juveniles, sub-adults and adults.